Factors influencing the adolescent pregnancy rate in the Greater Giyani Municipality, Limpopo Province - South Africa - Lenny Mushwana; Lydia Monareng; Solina Richter; Helene Muller (Elsevier, 2015)
A quantitative, descriptive and explorative survey was conducted to determine factors that influence adolescent pregnancy rate among teenage girls (n = 147) attending four high schools in the Greater Giyani Municipality in South Africa. Data was collected using a validated questionnaire which had a reliability of 0.65. Response frequency distributions, two-way frequency tables, Chi-square tests and Cochran-Armitage Trend Tests were used to determine the effect with the demographic characteristics of participants. Participants reported that health services were not conveniently available for them. Their relationship with nurses was poor (p < 0.05) as reported by 73% of participants with regard to maintenance of confidentiality. Participants reported key psychosocial variables such as inadequate sexual knowledge (61%), changing attitudes towards sex (58.9%) and peer pressure (56.3%) as contributory to high pregnancy rate. Recommendations were made to improve school health services, reproductive education in school curricula focussing on reproductive health, sexuality and guidance for future research.